Incidence of heart failure in 6083 elderly hypertensive patients: The Second Australian National Blood Pressure Study (ANBP2) - Sahle, B.; Owen, A.; Krum, H.; Reid, Christopher (2015)
© 2015 European Society of Cardiology. Aims: Hypertension is a known risk factor for the development of heart failure (HF); however, few data are available on the magnitude of short- and long-term progression from hypertension to HF. The present study aims to determine the short- and long-term incidence of HF, and identify factors associated with onset of HF in elderly hypertensive patients. Methods and results: The incidence of HF was measured in 6083 hypertensive patients, in the Second Australian National Blood Pressure Study (ANBP2), followed for a median of 10.8years (4.1years during the trial and 6.7years during post-trial follow-up). A total of 373 cases of HF were identified over 59 581 person-years of follow-up (PY). The overall cumulative incidence of HF was 6.26 per 1000 PY; 5.33 per 1000 PY during the ANBP2 clinical trial and 7.04 per 1000 PY during the post-trial follow-up. HF was 63% higher among men [incidence rate ratios (IRR) 1.63, P<0.01]. Older age, male sex, obesity, and history of cardiovascular disease independently predicted HF during both the short- and long-term follow-up. In addition, diabetes and smoking were associated with onset of HF in the short-term follow-up, and higher systolic blood pressure in the long-term follow-up. Median survival following diagnosis with HF was 3.94years, and women (6.06years) had a survival advantage over men (3.32years). Conclusion: Heart failure is a frequent long-term outcome in treated elderly hypertensive patients. Development of HF was predicted by patient characteristics and co-morbidities, with the effect of some predictors varying over the short- and long-term follow-up.